A Decade of Corporate Social Responsibility Research in Indonesia: A Bibliographic Study - Intan Kartika Sari; Y. Anni Aryani (Universitas Pasundan, 2023)
This paper aims to review the empirical literature on Corporate Social Responsibility (CSR) research in Indonesia, particularly in financial and accounting areas, for a decade from 2013 to 2022. The method used is bibliography research with charting the field approach. Empirical papers are collected based on electronic searches in nationally accredited journals. The keyword used to identify relevant studies is “corporate social responsibility” or “CSR”. This search yields 263 published papers from 35 nationally accredited journals over the period of 2013 to 2022. CSR research in Indonesia has developed significantly over the last 10 years. The study reveals that internal factors, such as company characteristics, financial performance, and ownership structure, are primarily considered leading variables of CSR research. The consequential variables of CSR that have been extensively researched are company value, financial performance, and tax aggressiveness. The most frequently used theories are the legitimacy theory and stakeholder theory. This study provides inspiration for future research direction to explore more about the determinants and implications of CSR. Future research can investigate the other variables that are still rarely observed, such as the relationship between CSR, digitalization, and employee-focused CSR research. The practitioners in the business field can comprehend more about CSR and improve CSR implementation. This study provides a comprehensive portrait of CSR research development in accounting and finance areas in Indonesia for a decade. Of 263 articles, this study analyses articles with quantitative methods as well as qualitative methods.